Experimental study on ductility improvement of reinforced concrete rectangular Columns retrofitted with a new fiber reinforced plastics method - 刘涛 冯伟 张智梅 欧阳煜 (Journal of Shanghai University, 2008)
Reinforced concrete （RC） columns lacking adequately detailed transverse reinforcement do not possess the necessary ductility to dissipate seismic energy during a major earthquake without severe strength degradation. In this paper, a new retrofit method, which utilized fiber-reinforced plastics （FRP） confinement mechanism and anchorage of embedded bars, was developed aiming to retrofit non-ductile large RC rectangular columns to prevent the damage of the plastic hinges. Carbon FRP （CFRP） sheets and glass FRP （GFRP） bars were used in this test, and five scaled RC columns were tested to examine the function of this new method for improving the ductility of columns. Responses of columns were examined before and after being retrofitted. Test results indicate that this new composite method can be very effective to improve the anti-seismic behavior of non-ductile RC columns compared with normal CFRP sheets retrofitted column.